Immune Cell and Biochemical Biomarkers in Advanced Laryngeal Cancer - Ana Jotic Ph.D., M.D; Jovica Milovanovic Ph.D., M.D; Katarina Savic-Vujovic Ph.D., M.D; Zorana Radin M.D; Branislava Medic Ph.D., M.D; Miljan Folic Ph.D., M.D; Bojan Pavlovic Ph.D., M.D; Aleksandar Vujovic M.D; Dusko Dundjerovic Ph.D., M.D (SAGE Publishing, 2022)
Objective The aim of this study was to evaluate cell and biochemical biomarkers and establish their prognostic value in patients with advanced laryngeal cancer. Material and Methods A prospective study included 52 patients with advanced laryngeal carcinoma surgically treated at the tertiary referral center. Tumor tissue was immunohistochemically stained for T-cell markers (CD4 and CD8), and levels of cytokines (IL-6 and IL-8) and C-reactive protein were analyzed from blood samples. Results Overall 3-year survival (OS) of patients included in the study was 69.2% and the disease specific survival (DSS) 72.5%. Higher expression of CD4 + and CD8 + were significant prognostic factors with positive impact on both OS and DSS in univariate analysis, but not in multivariate analysis. Levels of IL-8 were a significant predictor of 3-year OS and DSS survival in patients with advanced laryngeal cancer but not levels of IL-6 and CRP values. Conclusion Though high expression of CD4 and CD8 were demonstrated in the tumor tissue, but their prognostic role was not established. Higher values of IL-8 proved to be significant negative predictor of DSS. This could further collaborate the inclusion of combination of biomarkers in assessment of favorable treatment choice in patients with advanced laryngeal carcinoma.